A new species of the squat lobster genus Uroptychodes Baba, 2004 (Decapoda: Anomura: Chirostylidae) from Japan - Komai, Tomoyuki (Zootaxa, 2021)
A new species of the chirostylid squat lobster genus Uroptychodes Baba, 2004, U. fuscilineatus, is described and illustrated on the basis of a single ovigerous female from the Uraga Channel, central Japan, at depth of 250 m. The new species appears most similar to U. spinimarginatus (Henderson, 1885) and U. yapensis Dong, Gan & Li, 2021 among the 13 known congeners, but is notable in the pereopod 2 not being definitely more slender than the pereopods 3 and 4 and the remarkably spinose pereopods 1–4. A possible association of the new species with crinoid is suggested. An updated identification key to species of Uroptychodes is presented.